Peningkatan Kinerja Guru Dalam Menerapkan Model Pembelajaran Contextual Teaching And Learning (CTL) Melalui Kegiatan Supervisi Klinis - samilwati samilwati (Universitas Negeri Makassar, 2019)
. This study aims to determine the improvement of teacher performance in learning using the CTL learning model through clinical supervision in the Assistance Region I Kindergarten Pole Elo Mare District Bone Regency. This research is a School Action Research, because the research was conducted to solve the problem of the learning process at school and was carried out in 2 cycles with 2 meetings in each cycle. Based on the data analysis of the results of the study showed that the implementation of classroom supervision by the principal proved successful in improving teacher performance in managing the learning process by applying the contextual teaching and learning (CTL) learning model as evidenced by the increase in the results of observations made at 3 appraisers. In the aspects of the assessment of the Learning Implementation Plan (RPP) increased from 54.46 to 75.60 and 94.35 while the aspects of the assessment of the ability to plan learning increased from 54.63 to 70.83 and 87.96 and aspects of the ability to carry out learning, evaluation, and action continued from 55.77 to 68.91 and 81.73 at the end of the second cycle. Thus it can be concluded that the implementation of clinical supervision has proven to be effective in improving teacher performance in the Assistance Region I Kindergarten Pole Elo Mare District Bone in 2019 in applying the contextual teaching and learning (CTL) learning model.